A context aware system for driving style evaluation by an ensemble learning on smartphone sensors data. (April 2018) - Bejani, Mohammad Mahdi; Ghatee, Mehdi
Graphical abstract: Highlights: Evaluating the driving style based on smartphone sensors fusion. Using context-awareness to improve the performance of system. Extracting some parameters in three successive intervals of time to classify the maneuvers. Using an ensemble learning algorithm to classify the maneuvers. Applying a fusion method by using fuzzy rules to evaluate driver's styles. Abstract: There are many systems to evaluate driving style based on smartphone sensors without enough awareness from the context. To cover this gap, we propose a new system namely CADSE system to consider the effects of traffic levels and car types on driving evaluation. CADSE system includes three subsystems to calibrate smartphone, to classify the maneuvers, and to evaluate driving styles. For each maneuver, the smartphone sensors data are gathered in three successive time intervals referred as pre-maneuver, in-maneuver, and post-maneuver times. Then, we extract some important mathematical and experimental features from these data. Afterwards, we propose an ensemble learning method on these features to classify the maneuvers. This ensemble method includes decision tree, support vector machine, multi-layer perceptron, and k-nearest neighbors. Finally, we develop a rule-based fuzzy inference system to integrate the outputs of these algorithms and to recognize dangerous and safe maneuvers. CADSE saves this result in driver's profile to consider more for dangerous driving recognition. The experimental results show that accuracy, precision, recall, and F-measure of CADSE system are greater than 94%, 92%, 92%, and 93%, respectively that prove the system efficiency.